2006
DOI: 10.4141/a05-058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of B-vitamin supply on major metabolic pathways of lactating dairy cows

Abstract: Girard, C. L. and Matte, J. J. 2006. Impact of B-vitamin supply on major metabolic pathways of lactating dairy cows. Can. J. Anim. Sci. 86: 213-220. Knowledge of the major nutrient requirements of dairy cows has increased substantially during the past decades. Little is known, however, about the importance of the roles played by B vitamins. Since most of those vitamins act as essential cofactors in energy, protein and lipid metabolism, it is likely that as milk yield increases, the demand for these cofactors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…At least 10 different vitamin B12-dependent metabolic reactions have been identified in microorganisms. However, in mammals, only two important enzyme systems are recognized in which three vitamin B12-dependent enzymes participate: methylmalonyl CoA mutase and leucine mutase, which require adenosylcobalamin as a coenzyme, and methionine synthetase, which is required by the coenzyme methylcobalamin [ 1 , 7 , 10 , 12 , 15 , 16 , 19 , 24 , 27 , 28 , 29 ].…”
Section: Cobalt and Vitamin B12 Essential Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…At least 10 different vitamin B12-dependent metabolic reactions have been identified in microorganisms. However, in mammals, only two important enzyme systems are recognized in which three vitamin B12-dependent enzymes participate: methylmalonyl CoA mutase and leucine mutase, which require adenosylcobalamin as a coenzyme, and methionine synthetase, which is required by the coenzyme methylcobalamin [ 1 , 7 , 10 , 12 , 15 , 16 , 19 , 24 , 27 , 28 , 29 ].…”
Section: Cobalt and Vitamin B12 Essential Functionsmentioning
confidence: 99%
“…(1) The first, methylmalonyl CoA mutase, is a mitochondrial enzyme, dependent on cobalamin, involved in the metabolism of propionate to succinate. Methylmalonyl-CoA mutase catalyzes the transformation of methylmalonyl-CoA into succinyl-CoA, where 5′adenosylcobalamin functions as a coenzyme of the mutase, allowing the transformation of methylmalonyl CoA, which, in turn, comes from the propionate formed well as a product of ruminal fermentation, of the degradation of odd-chain fatty acids or of some amino acids: valine, isoleucine, methionine and threonine [ 25 , 28 ]. In ruminants, methylmalonyl-CoA plays a unique regulatory role in gluconeogenesis and fatty acid oxidation [ 30 ].…”
Section: Cobalt and Vitamin B12 Essential Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Santschi et al (2005b) assumed that ruminal niacin supply depends on diet composition, and that there are indications that the metabolism of supplemental niacin is influenced. Although it was presumed that ruminal niacin synthesis is sufficient for dairy cows with average performance level (Girard, 1998;GfE, 2001), this is possibly not always the case (Flachowsky, 1993;Girard & Matte, 2005;Breves & Lebzien, 2009). Weiss & Ferreira (2006) suggested that the requirements of dairy cattle tend to exceed the capacity of rumen microorganisms to synthesize sufficient amounts of vitamins of the B complex, owing to the improvement in the genetic potential of cows for higher milk yield.…”
Section: Introductionmentioning
confidence: 99%
“…Such an outcome could have been expected when considering experimental results — e.g. Bauman and Griinari ( 2010 ) reported that the diet-induced low-fat milk syndrome in dairy cows does not affect protein yield, while food supplementation with biotin increased milk yield, but showed only a limited effect on milk composition (Girard and Matte 1988 ). On the other hand, similarities between PKG and FKG/MKG were reported in studies where an averaged genetic effect was considered, e.g.…”
Section: Discussionmentioning
confidence: 78%